A new species of the predaceous midge genus Brachypogon Kieffer from the Neotropical Region and first description of the female of Brachypogon (Isohelea) cuacuahuitlus Huerta & Borkent (Diptera: Ceratopogonidae) - Huerta, Herón; Spinelli, Gustavo R. (Zootaxa, 2016)
The predaceous midge genus Brachypogon Kieffer is presently known in Mexico by Brachypogon (Brachypogon) fuscivenosus (Lutz, 1914), B. (B.) bimaculatus Spinelli & Grogan, 1998, B. (B.) woodruffi Spinelli & Grogan, 1998 and B. (Isohelea) cuacuahuitlus Huerta & Borkent, 2005. In this contribution a new species, Brachypogon (Brachypogon) ginue, is described and illustrated from a male specimen collected in Tlanchinol, State of Hidalgo, Mexico. This new species belongs to the impar species group. The first description of the female of Brachypogon (Isohelea) cuacuahuitlus Huerta & Borkent is also provided.